Classification Systems in Nursing: Formalizing Nursing Knowledge and Implications for Nursing Information Systems - Goossen, W. T. F.; Epping, P. J. M. M.; Abraham, I. L. (Methods of Information in Medicine, 1996)
The development of nursing information systems (NIS) is often hampered by the fact that nursing lacks a unified nursing terminology and classification system. Currently there exist various initiatives in this area. We address the question as to how current initiatives in the development of nursing terminology and classification systems can contribute towards the development of NIS. First, the rationale behind the formalization of nursing knowledge is discussed. Next, using a framework for nursing information processing, the most important developments in the field of nursing on formalization, terminology and classification are critically reviewed. The initiatives discussed include nursing terminology projects in several countries, and the International Classification of Nursing Practice. Suggestions for further developments in the area are discussed. Finally, implications for NIS are presented, as well as the relationships of these components to other sections of an integrated computerized patient record.
Keywords: Nursing Informatics; Nursing Records; Nursing Information Systems; Medical Records; Classification and Coding